Going to University - Case, Jennifer M.; Marshall, Delia; McKenna, Sioux; Disaapele, Mogashana (African Minds, 2021)
Around the world, more young people than ever before are attending university. Student numbers in South Africa have doubled since democracy and for many families, higher education is a route to a better future for their children. But alongside the overwhelming demand for higher education, questions about its purposes have intensified. Deliberations about the curriculum, culture and costing of public higher education abound from student activists, academics, parents, civil society and policy-makers.